Bianchi Type-I, III, V, VIo and Kantowski-Sachs universes in self-condition cosmology - Singh T.; Chaubey R. (My University, 2025)
The solution of Einstein's equation in presence of a self-creation cosmology in Brans-Dicke theory have been obtained for Bianchi type-I, III, V, VIo and Kantowski-Sachs (KS) universes in the quadrature form. Some physically interesting cases have been studied in detail.